2021
DOI: 10.32802/asmscj.2020.641
|View full text |Cite
|
Sign up to set email alerts
|

Perception Analysis of Industrialized Building System (IBS) Implementation for G7 Contractors in Kuching, Sarawak

Abstract: Industrialized Building System (IBS) is one of the initiatives underpinning the green construction zeitgeist. A myriad of advantages can be associated with adopting IBS in construction, including inter alia, improved construction quality and productivity, minimisation of construction waste, optimisation of construction materials on-site, enhanced environmental sustainability, and many others. In spite of these advantageous propositions, there is exist a gap in the exposure towards IBS construction methods, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…In reality, IBS adoption is still relatively low and still in the growing stages, as stated by Halil et al (2015) and Shukor et al (2011). This statement is also in line with the study by Abdullah et al (2021), where IBS implementation is still low in Sarawak, although the state government has strongly recommended it. According to Alawag et al (2021), the initiatives by the government to encourage the implementation of IBS also seem not to impact the adoption rate of IBS in Malaysia significantly.…”
Section: Low Adoption and Poor Performance Of Ibs In Malaysiasupporting
confidence: 70%
“…In reality, IBS adoption is still relatively low and still in the growing stages, as stated by Halil et al (2015) and Shukor et al (2011). This statement is also in line with the study by Abdullah et al (2021), where IBS implementation is still low in Sarawak, although the state government has strongly recommended it. According to Alawag et al (2021), the initiatives by the government to encourage the implementation of IBS also seem not to impact the adoption rate of IBS in Malaysia significantly.…”
Section: Low Adoption and Poor Performance Of Ibs In Malaysiasupporting
confidence: 70%
“…Studies have shown that costs are heavily impacted by a wide variety of variables, from the time of project estimation until the time of project completion. Studies by the previous studies [10][11][12][13], and others have found the elements that significantly influence construction costs in different nations. They argue that these aspects have a direct bearing on the construction organizations' responsibilities for managing the cost, socio-cultural, economic, external, technological, and political settings in which they operate, all of which have an impact on the construction costs.…”
Section: Introductionmentioning
confidence: 99%
“…Various stakeholders, such as developers, architects, engineers, contractors, and manufacturers, may have different opinions on IBS adoption, therefore it is critical to look at those stakeholders' objections. Even though there are numerous research has been done to examine the barriers to IBS uptake in Malaysia and other countries, most of the studies only obtained the opinions on the variables that restrict IBS uptake from the perspective of contractors only [6,11,14] and consultants only [4]. Other than that, most of the studies conducted on identifying the barriers of IBS implementation were done over a decade before and rather outdated [6,14,15].…”
Section: Introductionmentioning
confidence: 99%